(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This study examines the implementation of artificial intelligence (AI) technologies in extracurricular activities based on scientific research. Both international and local studies highlight AI’s pedagogical potential, its role in enhancing students’ independent learning, and the challenges associated with its integration. The study further presents evidence-based conclusions on effectively utilizing AI tools in organizing extracurricular educational activities.